By their works profiles of men of faith who made a difference - Singular, Stephen; Philip Lief Group (New York Collins, 2006)
Presents over sixty brief biographies of productive members of the Knights of Columbus society, including John F. Kennedy, "Babe" Ruth, and the founder of the society Father Michael J. McGivney.
"Produced by the Philip Lief Group, Inc."
Keywords: Knights of Columbus -- Biography